Radial augmentation index may be an effective predictor of vascular calcification in patients on peritoneal dialysis. Issue 1 (1st January 2020) - Yang, Ning; Yang, Wei; Cui, Wenting; Zhou, Dan; Du, Xiangning; Li, Longkai
Abstract: Vascular calcification (VC) is an important promoter of cardiovascular disease (CVD) in patients undergoing peritoneal dialysis (PD). Several indices can be used to evaluate VC, including the abdominal aortic calcification index (AACI) and carotid artery intima–media thickness (IMT); however, simpler and lesser expensive predictors, such as the radial augmentation index (RAI), should be investigated. A total of 101 patients undergoing PD were recruited to measure RAI, AACI, and carotid artery IMT and perform echocardiography. Fifty healthy controls (HCs) were recruited to undergo RAI measurement. RAI in patients undergoing PD was significantly higher than the RAI in HCs (86.25%±8.39% vs. 76.05%±9.81%, p < 0.05). Patients undergoing PD and who suffer with diabetic mellitus, hypertension, and CVD had more severe VC than those without the abovementioned diseases. In patients with PD, RAI was positively correlated with AACI ( r = 0.671, p < 0.05) and carotid artery IMT ( r = 0.596, p < 0.05). RAI was positively correlated with left ventricular end-diastolic dimensions (LVDd; r = 0.678, p < 0.05), left ventricular mass index ( r = 0.595, p < 0.05), and negatively correlated with early-diastolic mitral inflow velocity/late-diastolic mitral inflow velocity ( r = −0.342, p < 0.05) and left ventricular ejection fraction ( r = −0.497, p < 0.05). Multiple linear regression analysis showed that RAI was associated with AACI, LVDd, age, and serum phosphate ( p < 0.05). RAI might be an effective predictor of VC and cardiac structural/functional abnormalities in patients undergoing PD.